تناقض الأحكام المنظمة لأسباب عدم صحة عقد الزواج في قانون الأسرة الجزائري - شندارلي, توفيق (جامعة الوادي University of Eloued, 2019)
يشترط لإبرام عقد الزواج توافر جميع مقوماته وشروطه، فإذا استوفى جميع ما يتطلب فيه لتكوينه، كان العقد صحيحا، و ترتبت عليه، فور تمامه، جميع آثاره بالنسبة للمتعاقدين و لغيرهما. و بالمقابل إذا تخلفت احدى هذه المتطلبات كان العقد غير صحيح، و لا يترتب عنه أي أثر من تلك الآثار. لكن هذه المتطلبات ليست على درجة واحدة من الأهمية، فإذا كان تخلف بعضها يؤثر في وجود العقد في حد ذاته، فيكون باطلا، أي منعدما، فإن البعض الآخر لا يؤثر في وجوده، بل يؤثر في صحته، فيكون فاسدا، و من ثمة يجب تحديد و معرفة أسباب البطلان و تمييزها عن أسباب الفساد على وجه الدقة. إذن فالباطل معدوم، لا يمكن أن يرتب أثرا و إن حصل دخول بالزوجة، أما الفاسد فهو موجود لكنه معتل، يعترف فيه ببعض الآثار الضرورية إن حصل دخول بالزوجة باعتباره واقعة مادية فقط، وإن كان في الحالتين يجب التفريق بين الزوجين، لأن العقد جاء على غير الصورة التي أمر بها القانون. The contract of marriage requires the availability of all its pillars and conditions. If all the requirements for its composition have been met, the contract is valid once it has been completed, and all of its effects on the contractors and others. On the other hand, if one of these requirements fails, the contract is incorrect and does not have any effect. But these requirements are not at the same degree of importance, if the failure of some of these requirements affects the existence of the contract in itself, and it becomes null, others do not affect its existence, but affects its health, and it becomes corrupt. and from there they it must be identified exactly, to know the causes of the invalidity, and to distinguish them from the causes of corruption. Therefore, the invalid contract is null, and there can be no effect even if there is a consummation. on the other hand, if there is a corrupt contract, it is still existing but it has an effect on it health, in which law admits some necessary effects if there is a consummation as material fact only. although in both cases it must be a differentiate between the spouses, because the contract came as opposed to the form ordered by the law.
The Contradicting Provisions For The Causes Of The The Incorrect Marriage In The Algerian Family Code
Keywords: عدم صحة الزواج ; العقد الفاسد ; العقد الباطل ; أسباب الفساد ; أسباب البطلان ; الشروط الباطلة ; موانع الزواج ; الشروط الخاصة بعقد الزواج; incorrect marriage ; corrupt contract ; invalid contract ; causes of corruption ; causes of invalidity ; invalid conditions ; marriage barriers ; special conditions for marriage contract